The Development of the Clay Tobacco Pipe Kiln in the British Isles - Allan Peacey (Internet Archaeology, 1996)
In 1982 Allan Peacey published a study in the form of a synthesis of two chronologically separated kilns used in the production of clay tobacco pipes (Peacey 1982, 3-17). The aims of the present work are: ◦to improve upon this framework ◦to establish how these type of structures fit into the broader picture; to fill the gaps, before, between and after these cameo views ◦to improve understanding of the technology employed and see the roots from which such technology developed.